Bioaktivitas dan Identifikasi Molekuler Jamur yang Diisolasi dari Sedimen di Pantai Amed dan Tulamben - Wulandari, Ni Made Widya; Dwijayanti, Ni Kadek; Putri, Ni Putu Ananda Eka; Putra, I Putu Yogi Astara; Leliqia, Ni Putu Eka; Wibowo, Joko Tri; Dwija, Ida Bagus Nyoman Putra; Ariantari, Ni Putu (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
Marine fungi have demonstrated the ability to produce promising new bioactive compounds. This study aims to isolate fungi from the marine sediments collected from Amed and Tulamben Beaches, Bali, Indonesia and investigate the bioactivity of the fungal extracts. Following fungal isolation, pure isolates were obtained and fermented on rice media containing salt and without salt. Next, secondary metabolites were extracted with ethyl acetate, then separated by liquid-liquid extraction using methanol containing 10% water and n-hexane. The resulting MeOH extracts were analyzed for their phytochemical content and tested for their antimicrobial and antioxidant activities using the disc diffusion and 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, respectively. In total, three fungal isolates were obtained. Molecular identification from the Internal Transcribed Spacer (ITS) region of the isolates showed the closest relationship to Aspergillus sp., Aspergillus tamarii, and Trichoderma sp. Phytochemical analysis showed all fungal extracts contained alkaloids and polyphenols. Moreover, extract from Trichoderma sp. SED-TU (1) (NS) inhibited Staphylococcus aureus, Staphylococcus epidermidis, and Streptococcus mutans with inhibition zone diameters of 4.69±0.16; 3.51±0.01, and 3.49±0.25 mm, respectively. Extract from Aspergillus tamarii RM-S-SED-AM (S) inhibited Candida albicans with an inhibition zone of 7.04±0.22 mm and also had strong antioxidant activity with an IC50 value of 62.00±0.35 µg/mL. This study indicates that fungal isolates from marine sediments have great potential as a source of bioactive natural products.